Molecular conductance of double-stranded DNA evaluated by electrochemical capacitance spectroscopy - Ribeiro, W. C. [UNESP]; Goncalves, L. M.; Liebana, S.; Pividori, M. I.; Bueno, P. R. [UNESP] (Royal Soc Chemistry, 2016)
Conductance was measured in two different double stranded DNA (both with 20 bases), the more conducting poly(dG)-poly(dC) (ds-DNAc) and the less conducting poly(dA)-poly(dT) (ds-DNAi), by means of Electrochemical Capacitance Spectroscopy (ECS). The use of the ECS approach, exemplified herein with DNA nanowires, is equally a suitable and time-dependent advantageous alternative for conductance measurement of molecular systems, additionally allowing better understanding of the alignment existing between molecular scale conductance and electron transfer rate.